The spiders of the genus Wolongia Zhu, Kim & Song, 1997 from China (Araneae: Tetragnathidae) - Wan, Jin-Long; Peng, Xian-Jin (Zootaxa, 2013)
Seven new species of spiders of the genus Wolongia, all from China, are described. This genus previously included only three species, also only known from China. The new species are: Wolongia bicruris n. sp., Wolongia bimacroseta n. sp., Wolongia erromera n. sp., Wolongia foliacea n. sp., Wolongia mutica n. sp., Wolongia renaria n. sp., and Wolongia tetramacroseta n. sp. Descriptions of the seven new species and diagnoses for all ten species in the genus are given. In addition, we provide distributional data and an identification key to the species.